Réponses physiologiques à l`exercice en altitude modérée: intérêt de la mesure de la SpO2 - Gaston, A.-F.; Roca, E.; Doucende, G.; Hapkova, I.; Subirats, E.; Durand, F. (Science & Sports, 2016)
Aim: To predict the effect of moderate altitude exposure on performance and cardiorespiratory adaptations in order to provide recommendations to endurance trained athletes who want to perform exercise at moderate altitude. Method: Fifteen endurance trained athletes have performed an incremental maximal exercise at sea level and at 2150 m. Haemoglobin oxygen saturation (SpO2), gas exchanges and heart rate (HR) were recorded continuously during the tests. Results: HR at ventilatory threshold (VT) was lower at moderate altitude compared to sea level: -13 ± 3.4 bpm at VT1 and -7 ± 1.5 bpm at VT2 (P < 0.01). Power output was also decreased by around 40watts at both VT1and VT2 (P < 0.01). Seven athletes showed a significantly drop in SpO2 at the end of exercise at sea level (exercise induced hypoxemia [EIH]). Maximal oxygen uptake ( VO2max ) at altitude was decreased by 22 ± 2.9% in EIH athletes and by 15 ± 1.9 % in non-EIH athletes (P < 0.01). EIH athletes showed a significantly decrease in HRmax at altitude (-8 ± 3.3 bpm, P < 0.05). A correlation was found between the decrease in VO2max and two others variables, the decrease in HRmax at altitude and the training load. Conclusion: This study points out the importance of SpO2 measurement during exhaustive ramp test at sea level for athletes who want to perform at altitude. Indeed, athletes with a significantly drop in SpO2 at sea level present a greater decrease in VO2max and HRmax at moderate altitude. However, HR and power output at VT must be adjusted during acute exposure to moderate altitude for all athletes.